GENDER AND CONSTITUTIONAL LAW IN AUSTRALIA AS A CONSIDERATION FOR INDONESIA - Dwi Rahayu Kristianti (Yuridika, 2010)
Women’s inequality seems to be a product of political, legal, cultural and religious forces. Research has been conducted on the experience of gender equality of other countries, in this case, Australia. The promotion of gender equality through the politico-legal process,especially through its Constitution and legislation, has resulted in significant progress for women in Australia. This article uses gender analysis. The Australian constitution will be analyzed in in a gendered way. It is expected that the findings may assist in improving the constitutional framework for the protection of women’s rights in Indonesia. Thus, the aim of this paper is to question how Indonesia can learn from a liberal democratic state to empower women through constitutional amendments or other politico-legal processes.